Tax planning: a case study of a footwear company to identify the most advantageous tax regime (Research, Society and Development, 2020)
In the face of a world that’s becoming more and more globalized, with fast and meaningful changes, especially in regards to legislation, and in a country such as Brazil with a considerable tax burden, enterprises are looking for tools to boost their competitiveness in the market. Tax planning comes into scene as an important tool for enterprises and this project aims to explain the most commonly used tax regimes in Brazil, demonstrating when each must be used. Since this study is based on real data, an assessment between the Simples Nacional and Inferred Profit regimes was chosen to expose which one of these is more beneficial for the enterprise. Data from a Shoes Industry from Nova Serrana City were analyzed between the years of 2016, 2017 and the period from Jan 1st to Jun 30th of 2018, in which accounting documents and other relevant tools were used, demonstrating the impacts of taxes over said industry and the importance of tax benefits. Considering the results, we concluded the company analyzed in this case study was in fact in already under the most beneficial tax regime, which was the Presumed Profit. In view of fiscal benefits conceded to the enterprise today could be extinct, it was made a comparison without the aforementioned benefits, which presented a different result. These benefits include a Special Regime of taxation conceded to the Shoes Manufacturers of Minas Gerais State, linked directly to ICMS and Payroll Exemption, conceded though the Law 12.546, of Dec 14th 2011, linked to CPRB, both to Presumed Profit adherers. In this case, without such tax benefits for the Presumed Profit Regime, the Simples Nacional tax regime presents a more favorable scenario for the enterprise.